Description of Factors that Influence Medication Compliance in Hypertension Patients at the Separi 3 Kutai Kartanegara Health Center - Sholichin, Sholichin; Exlesia, Sarah; Rining, Marina Kristi Layun; Khumaidi, Khumaidi; Syahrun, Syahrun (Fakultas Kedokteran, 2023)
Hypertension is a lifelong disease that cannot be permanently cured but can only be controlled by controlling blood pressure by managing a healthy lifestyle and taking recommended antihypertensive drugs. Purpose: this study is to describe the factors of knowledge, family support, and access to health facilities that influence medication adherence in hypertensive patients at the Separi Health Center. Methods: this study used a descriptive research design with a cross sectional approach. The sampling technique used is probability sampling technique with proportional stratified random sampling method with a total sample of 84 respondents. Results: the study showed that 82.1% of patients did not adhere to taking medication, and 17.9% of patients adhered to taking medication. Patients with less knowledge 31.0% and patients with good knowledge 69.0%. Patients with poor family support 56.0% and patients with good family support 44.0%. Patients with poor access to health services 46.4% and patients with good access to health services 53.6%. Conclusion: the results of the study show that despite having good knowledge, family support, and access to health services, most patients do not adhere to taking medication. Suggestions for existing health services are expected to improve service quality and provide information and education to people with hypertension.